FREQUENCY OF CORONARY ARTERY DISEASE IN PATIENTS WITH CHRONIC HEART BLOCKS, CANDIDATES FOR PERMANENT PACEMAK-ER IMPLANTATION - Yones Nozari; Omid Hashemifard; Fariba Mollaii (ARYA Atherosclerosis, 2010)
Abstract BACKGROUND: Coronary artery disease (CAD) is associated with chronic heart blocks. The purpose of this study was to find the frequency of CAD in four major types of cardiac conduction disorders i.e.: Sick Sinus Syndrome (SSS), 2nd degree atrioventricular (AV) block, complete heart block (CHB) and bifasicular and trifasicular blocks. METHODS: During this one- year study, we performed coronary angiography (CAG) in all patients with above mentioned conduction defects, who have been hospitalized for permanent pacemaker implantation; we determined the frequency of various degrees of CAD in different types of heart blocks. RESULTS: 34 patients (64%) had no significant lesion in CAG, 20 (36%) had above 50% stenosis in at least one major coronary artery branch with 13% mono-vessel disease ,9.3% two- vessel disease and 14.8% three-vessel disease. Overall, 13 patients (24%) had critical CAD. CONCLUSION: CAD is common in patients with chronic conduction defects and might have a causative role in this regard. Keywords: Coronary artery disease, Chronic conduction defect, Coronary angiography.